Pemberhentian Direktur Tanpa Kesempatan Membela Diri Melalui RUPSLB: Studi Kasus Putusan Nomor 143/Pid.B/LH/2020/PN Sdw - Kaltzum Salzabiela A Paseng (Lembaga Pengembangan Kinerja Dosen, 2025)
The dismissal of a director from his position, based on article 105, is carried out through a GMS. According to article 78 of the PT Law, a GMS consists of an annual GMS and other GMS. Other GMS, as explained in article 78 paragraph 1, in practice, are known as Extraordinary GMS (EGMS). Unlike the annual GMS, an EGMS can be held at any time, based on the needs for the benefit of the company. Based on the trial facts in the decision of the West Kutai District Court regarding the discovery of facts about the dismissal and replacement of directors at PT Sendawar Adhi Karya. It is known that the dismissal and replacement of Agus Basuki from the position of director of PT Sendawar Adhi Karya is not in accordance with the mechanism regulated in the provisions of Law number 40 of 2007 concerning Limited Liability Companies. Thus, the provisions in the articles of association regarding changes to the management structure of PT Sendawar Adhi Karya are considered never to have existed.